Offshoring insect farms may jeopardize Europe's food sovereignty - Ren Ryba (Global Sustainability, 2024)
Abstract Non-technical summary Given increasing global political, security and economic challenges, politicians in the European Union (EU) are seeking to reduce the EU's dependence on imports, including feed for farmed livestock. While insect farming has been suggested as an advantageous source of livestock feed is the insect farming industry, the sector has not met optimistic expectations. In particular, labor and electricity costs are driving insect companies offshore, including to Asia and the United States. This paper explores ways that the EU could solve this problem, the most promising of which is to expand the EU's production of maize and soy.